PENINGKATAN MUTU BIJI KOPI RAKYAT DENGAN PENGOLAHAN SEMI BASAH BERBASIS PRODUKSI BERSIH - Elida Novita; Rizal Syarief; Erliza Noor; Sri Mulato (JURNAL AGROTEKNOLOGI, 2010)
Application of semi-wet processing in coffee post harvest is one effort to improve smallholder coffee bean quality, eventhough produce wastewater that harmfull for environmental. By implementing cleaner production concept with water minimization could solve environmental problems while maintaining the coffee bean. The purpose of this study was to determine the effect of semi-wet processing based on water minimization on coffee quality. Coffee berries are treated by minimize water design to produce coffee bean. Quality testing includes water content analysis, physical quality test based on SNI standards and cup test (sensory test). Coffee bean samples from semi-wet processing are compare with coffee bean from dry process and Sidomulyo smallholder. The results showed selective picking during harvest and semi-wet processing affects physical quality. Water process minimization showed no difference on physic and sensory quality of coffee beans. Though physical assessment cannot fully guarantee the beverage quality, but could anticipate most of defects flavored coffee drink. Conversely, the error in estimating of coffee taste based on physical properties can be minimized by cup test. Although, the sensoric assessment is subjective likely, but the cup test showed there is effect of semi-wet processing to the quality of coffee drinks as a final product.Keywords: coffee quality, coffee bean, semi-wet processing, water minimization, cleaner production